Strategi Penguatan Hukum Perlindungan Konsumen Dalam Era Digital - M. Elpha Darnia; E. Enjely Utami; R. Marsya; D. Permata Pertiwi; N. Nadila; H. Setian; M. Irsal (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Consumer protection law is a law that contains regulatory principles and also contains characteristics that protect the interests of consumers. Consumer protection law is also one of the aspects that creates a sense of security and comfort in buying and selling activities. Consumer protection law is the totality of principles and rules that regulate and protect consumers. Even though it is intended to protect the interests of consumers, the Consumer Protection Law does not aim to kill business actors. With the Consumer Protection Law, business actors are expected to be more motivated to increase their competitiveness by paying attention to consumer interests. Consumer protection law is very important for sellers as business actors, because it can prevent sellers from doing things that are prohibited by law and can also prevent losses for buyers as consumers. If sellers understand consumer protection laws, they will not violate these laws and sell seedlings according to the rules that have been set.